2002
DOI: 10.1016/s0002-9440(10)61163-7
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Lesions Grow Through Recruitment and Proliferation of Circulating Monocytes in a Murine Model

Abstract: Macrophage-derived foam cells in developing atherosclerotic lesions may potentially originate either from recruitment of circulating monocytes or from migration of resident tissue macrophages. In this study, we have determined the source of intimal macrophages in the apoE-knockout mouse flow-cessation/hypercholesterolemia model of atherosclerosis using a bone marrow transplantation approach. We also examined the time course and spatial distribution of intercellular adhesion molecule-1 and vascular cell adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 26 publications
5
101
2
1
Order By: Relevance
“…27 GaL3 was shown to mediate the endocytotic uptake of modified lipoproteins 15 and to be a component of the AGE-receptor complex expressed in macrophages. 16 The functional interaction of GaL3 (AGE-R3) with AGE-R1 and AGE-R2 receptors 28 suggested the possible interaction with AGEbinding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…27 GaL3 was shown to mediate the endocytotic uptake of modified lipoproteins 15 and to be a component of the AGE-receptor complex expressed in macrophages. 16 The functional interaction of GaL3 (AGE-R3) with AGE-R1 and AGE-R2 receptors 28 suggested the possible interaction with AGEbinding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…High-fat Diet-induced EC TJ Disassembly Enhances Monocyte Adhesion-Although endothelial dysfunction marks the initiation of atherosclerosis (26), the recruitment of monocytes to this site "seeds the soil" for the disease pathogenesis (43,44). It has been reported that the areas with endothelial hyperpermeability on the luminal side of the artery recruit circulating monocytes (44).…”
Section: (S)-hete Disassembles Endothelial Tight Junctions Observed Inmentioning
confidence: 99%
“…It has been reported that the areas with endothelial hyperpermeability on the luminal side of the artery recruit circulating monocytes (44). Based on this information, we applied two approaches to find out whether 12/15-LO-mediated EC TJ disruption results in the recruitment of monocytes.…”
Section: (S)-hete Disassembles Endothelial Tight Junctions Observed Inmentioning
confidence: 99%
“…Monocytes/macrophages play important roles in the development of atherosclerosis. Circulating monocytes migrate under the subendothelial space and differentiate into macrophages as a key inflammatory response in the development of atherosclerotic lesions (3,4). As a result of activation, macrophages release a host of pro-inflammatory mediators, including tumor necrosis factor (TNF), interleukins (IL) and several kinds of proteases, such as the matrix metalloproteinases.…”
Section: Introductionmentioning
confidence: 99%